Multi-Country Report : Building Fiscal Capacity in Fragile States-Case Studies-Press Release; Staff Report. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This report reviews the IMF's effort to build fiscal capacity in fragile states. It presents case studies on IMF technical assistance (TA) and capacity development in the fiscal area, provided by its Fiscal Affairs Department in collaboration with the Legal Department, in countries including Afghanistan, Haiti, Kosovo, Liberia, Mali, Myanmar, South Sudan, and Timor-Leste. The details in the case studies in various areas of fiscal policy management shed light on country-specific characteristics, how well IMF TA helped countries address fiscal capacity in the past, and lessons learned that could improve TA strategies and delivery in the future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet